Evaluation of Newborns Diagnosed with COVID-19: A Single-Center Experience - Aydoğan, Seda; Zenciroglu, Aysegul; Çitli, Rumeysa; Dilli, Dilek; Özdem, Suna (American Journal of Perinatology, 2022)
Objective The causative agent of the severe acute respiratory syndrome is a new type of coronavirus infection called coronavirus disease-2019 (COVID-19) which has spread around the world. COVID-19 is thought to rarely affect infants, so pandemic planning focuses on adults. This study aimed to share our 1-year experience with COVID-19-positive newborns in a tertiary neonatal intensive care unit (NICU).Study Design Hospitalized newborns after a reverse transcription polymerase chain reaction (RT-PCR) for COVID-19 were evaluated in this retrospective, cohort study between March 2020 and March 2021. The clinical course, laboratory tests, imaging studies, and outcomes of affected newborns were collected from medical records.Results Eleven COVID-19-diagnosed newborns were analyzed in our study. Four (36.6%) patients had contact with a COVID-19-positive individual in their families. The main symptoms were fever (81.8%), hypoxemia (63.6%), and tachypnea (63.6%). Bacterial coinfection was identified in two newborns. Aortic coarctation was detected as an accompanied disease by a newborn who was referred to our hospital with a suspicion of congenital heart disease and two patients had a bacterial coinfection. We did not detect any cases of neonatal multisystem inflammatory syndrome. All patients were discharged in good health. None of the newborns had any complications and repeated infection with another variant during the first-year follow-up.Conclusion Contrary to popular belief, newborns are a sensitive age group for COVID-19 and need a high rate of hospitalization. Congenital heart diseases and coinfections should not be overlooked in COVID-19-infected newborns. The acquired immunity due to COVID-19 infection protects newborns from recurrent COVID-19 infections in their first year of life. The absence of COVID-19-positive individual in the family in most cases suggests that PCR-negative adults may also play a role in the transmission of the disease.Key Points
Keywords: COVID-19; newborn; outcomes; symptoms